2012
DOI: 10.1097/prs.0b013e31824ec411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immediate Implant Placement versus the Staged Tissue Expander Technique in Breast Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 20 publications
5
47
2
Order By: Relevance
“…1,4,19,23,26 Six studies compared patient demographics and operation-related characteristics between two groups. 1,[3][4][5]18,19 Of these, a study by Petersen et al 5 showed unilaterally unfavorable patient characteristics in which the one-stage group included a significantly higher rate of smokers and obese patients, which resulted in significant heterogeneity in the analysis. Therefore, we…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…1,4,19,23,26 Six studies compared patient demographics and operation-related characteristics between two groups. 1,[3][4][5]18,19 Of these, a study by Petersen et al 5 showed unilaterally unfavorable patient characteristics in which the one-stage group included a significantly higher rate of smokers and obese patients, which resulted in significant heterogeneity in the analysis. Therefore, we…”
Section: Resultsmentioning
confidence: 97%
“…1,3-5,13,16-18,20-28 Nine studies were conducted with patients who underwent NSM, 13,[16][17][18][20][21][22]24,25 three for skinsparing mastectomy 5,27,28 and one for both. 3 The other five studies did not describe the specific mastectomy types used, and they likely included cases of non-NSM. 1,4,19,23,26 Six studies compared patient demographics and operation-related characteristics between two groups.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations